TRANSFORMASI NILAI KARAKTER MELALUI KETELADANAN GURU DI LINGKUNGAN SEKOLAH DASAR - Nadziroh Nadziroh (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2023)
Character education is a fundamental aspect in shaping students’ personalities from an early age. In the context of elementary schools, teachers play a central role as role models who can transform character values through their daily behavior and interactions. This study aims to describe how teacher role modeling contributes to the formation and transformation of students’ character values at SD Negeri Badran Yogyakarta. This research employed a qualitative approach with data collected through interviews, observations, and documentation. The participants included students, a religious education teacher, and the school principal. Data were analyzed descriptively by interpreting the findings based on character education theory. The results indicate that teachers who demonstrate exemplary behavior in dress, discipline, responsibility, tolerance, friendliness, cleanliness, and social care are able to effectively instill character values in students. Such role modeling is not only imitated by students but also shapes their positive attitudes and behaviors in everyday school life. These findings suggest that teacher role modeling is an effective strategy in character education and should be consistently integrated into elementary school learning practices.